Effect of oceanic turbulence on the statistical features of electromagnetic optical beam - Hemant Kumar Singh; Vikram Singh Bhandari; Bhaskar Kanseri (Results in Physics)
This work deals with the intricate problem of electromagnetic optical beam propagation through oceanic turbulence. Using the extended Huygens–Fresnel principle, numerically, the behavior of the degree of cross-polarization (DOCP), electromagnetic degree of coherence (EMDOC), and also the newly introduced Stokes scintillation parameters are explored through the oceanic turbulence medium. In contrast to atmospheric turbulence, oceanic turbulence introduces complexity in optical beam propagation due to additional variables, such as temperature-salinity fluctuations, the energy dissipation rate, etc. We investigate the fact that during propagation through oceanic turbulence, these parameters are affected differently. The outcomes reveal that changing the coherence and polarization of the input source allows control over these parameters during propagation through oceanic turbulence. Furthermore, we observed that the oceanic turbulence factors, such as temperature fluctuations, rate of dissipation of energy, etc., significantly impact the statistical properties of the vectorial light beams. The implications of these findings are relevant in underwater communication, imaging, remote sensing, and other related applications.